Paraoxonase promoter and intronic variants modify risk of sporadic amyotrophic lateral sclerosis. Issue 9 (16th August 2007) - Cronin, Simon; Greenway, Matthew J; Prehn, Jochen H M; Hardiman, Orla
Abstract : Background: The paraoxonases, PON1–3, play a major protective role both against environmental toxins and as part of the antioxidant defence system. Recently, non-synonymous coding single nucleotide polymorphisms (SNPs), known to lower serum PON activity, have been associated with sporadic ALS (SALS) in a Polish population. A separate trio based study described a detrimental allele at the PON3 intronic variant INS2+3651 (rs10487132). Association between PON gene cluster variants and SALS requires external validation in an independent dataset. Aims: To examine the association of the promoter SNPs PON1−162G>A and PON1−108T>C ; the non-synonymous functional SNPs PON1Q192R and L55M and PON2C311S and A148G ; and the intronic marker PON3INS2+3651A>G, with SALS in a genetically homogenous population. Methods: 221 Irish patients with SALS and 202 unrelated control subjects were genotyped using KASPar chemistries. Statistical analyses and haplotype estimations were conducted using Haploview and Unphased software. Multiple permutation testing, as implemented in Unphased, was applied to haplotype p values to correct for multiple hypotheses. Results: Two of the seven SNPs were associated with SALS in the Irish population: PON155M (OR 1.52, p = 0.006) and PON3INS2+3651 G (OR 1.36, p = 0.03). Two locus haplotype analysis showed association only when both of these risk alleles were present (OR 1.7, p = 0.005), suggesting a potential effect modification. Low functioning promoter variants were observed to influence this effect when compared with wild-type. Conclusions: These data provide additional evidence that genetic variation across the paroxanase loci may be common susceptibility factors for SALS.